Patient-reported assessment of compassion in Spanish: a systematic review - Soto-Rubio, Ana; Picazo, Carmen; Gil-Juliá, Beatriz; Andreu-Vaillo, Yolanda; Pérez-Marín, Marian; Sinclair, Shane (Frontiers in Medicine, 2024)
Aims and objectives: This systematic review aims to: 1) explore which tools have been used in Spanish to measure compassion; 2) know which of these tools could be used to assess compassion in healthcare settings from the perspective of patients; 3) evaluate the quality of these patient-reported measures in Spanish contexts; and 4) determine which of these instruments would be best suited to be used in healthcare settings. Background: Compassion has been recognized as a fundamental dimension of quality healthcare. Methods: Several scientific databases were consulted for relevant records published up to December 16 th , 2021.In accordance with PRISMA guidelines, 64 studies were included. Results and conclusions: while existing instruments, validated in Spanish, allow for the measurement of selfcompassion or compassion to others, there are no valid and reliable measures currently